MENINGKATKAN KEMAMPUAN BERBICARA BAHASA INGGRIS DENGAN STRATEGI MANDATORY PARTICIPATION MELALUI VARIASI PUBLIC SPEAKING PERFORMANCES PADA MAHASISWA SEMESTER III DI STAIN PAMEKASAN - Virdyna, Nina Khayatul (STAIN PAMEKASAN, 2015)
English role as foreign language in Indonesia is extremely significant. Studentsâ participation in learning process is very important to create active, creative and enjoyable learning process. Researcher endeavours to increase studentsâ participation in speaking class by Mandatory Participation Strategy through public speaking performance variation. This strategy can force students to be fully participating in the speaking class. Furthermore, research focus of this research is; âHow Mandatory Participation Strategy through public speaking performance variation increase speaking English ability of students at Semester III in STAIN Pamekasan? This research is designed classroom action research namely Practical Action Research. Researcher endeavours to increase studentsâ participation in speaking class by mandatory participation strategy through public speaking performance variation.This research conducted in two cycles, those are cycle I and cycles II. Every cycle consists of 4 meeting. In every meeting, it will be conducted mandatory participation strategy through public speaking performance variation. There is significant increasing from speaking pre test score which is conducted in initial research with after applying mandatory participation in public speaking performance in cycle I. 60% students in cycle I fulfil passing grade standard.In the result of cycle II, there is significant increasing from the score of cycle I after applying mandatory participation in public speaking performance revision version. 77% students in cycle II fulfil passing grade standard. The strategy in cycle II is more successful in increasing studentsâ speaking skill. Students are more actively speak if they think they express freely. In conclusion, there is 10% upgrading till 17% in cycle II.Â